Innovative catalyst design for the oxygen reduction reaction for fuel cells - Shimizu, K; Sepunaru, L; Compton, R (Royal Society of Chemistry, 2016)
A combination of chemical and electrochemical catalysis is introduced herein as a new approach to overcome one of the most challenging and persistent issues in fuel cell cathodes. Demonstrated using hematite (a-Fe2O3) nanoparticles modified glassy carbon electrode, this bifunctional fuel cell catalyst system prevails the slow kinetics of the oxygen reduction reaction by rapid heterogeneous disproportionation of hydrogen peroxide. Whilst the catalytic efficiency of glassy carbon is limited to the two-electron reduction of oxygen, modification with hematite drastically improves it to equivalent to the four-electron pathway. This is due to regeneration of the cathodic fuel through the rapid decomposition of hydrogen peroxide. The importance of such system is stressed as the formation of water rather than hydrogen peroxide is essential to maximize the energy output of the fuel cell. Cycling of oxygen reduction/regeneration boosts the activity of a low-cost catalyst to be comparable to that of platinum and concurrently reduces the risk of cell degradation.